Evaluating the Efficiency of Finance Methods in Residential Complex Projects in Iraq - Khameesa, A. S.; Altaay, M. R. (Engineering, Technology & Applied Science Research, 2022)
Financial funding of a construction firm plays an important role in all aspects of the process development. It has been noted that financial crises have a direct impact on the construction industry. The Iraqi government, whether locally or globally, has faced a severe shortage of financing which has resulted in incomplete projects. Due to the financial crisis that Iraq went through which led to the suspension of many residential complex projects and the difficulty of the use of public financing methods, we researched the private financing (public-private partnership) methods instead of public financing methods in residential complex projects implementation. This study verified the financial problems and the factors that relate to the possibility of their occurrence with the use of a questionnaire that was designed and distributed to professionals in the field. Arbitration of the questionnaire, pilot study, questionnaire distribution, and statistical tests were conducted. The T-test (paired samples T-test) was used to find out if there are differences between the public and private financing methods. The results showed that the private financing (public-private partnership) methods, under the current conditions in Iraq, are better than the public financing methods.